Caracterização bioquímica de duas quitinases recombinantes do cajueiro (Anacardium occidentale L.) das classes IV e VI com atividade antifúngica - Oliveira, Simone Torres de (2020)
Chitinases are enzymes capable of hydrolyzing the -(1,4) covalent bonds between the Nacetyl- -D-glucosamine (GlcNAc) residues that make up chitin. The polysaccharide chitin, being a structural component of the fungal cell wall, led to an interest in enzymes that degrade chitin, in order to develop antifungal products. The presence of chitinases in the cashew tree (Anacardium occidentale) was found experimentally in the exuded gum from the tree. In addition, transcripts encoding chitinases of the GH1λ family were identified in the CCP 76 dwarf cashew seed transcriptome and two of these chitinases, AoChi4κ4λ and AoChi547β, were selected for this work. An initial analysis of chitinases revealed a mutation at its catalytic site AoChi547β, where a Glu residue, essential for enzymatic catalysis, was replaced by a Lys residue. Thus, the objective of this work was to verify the functionality of these chitinases with respect to the ability to degrade chitin and to investigate the antifungal and antibacterial activity of recombinant proteins. Bioinformatics and phylogenetic analyzes showed that AoChi4κ4λ belongs to the class I↑ of chitinase and AoChi547β to the class ↑I. Notably, all Class ↑I representatives also present Lys as a catalytic amino acid. Molecular docking analysis performed with the catalytic domain of AoChi547β and (GlcNac)4 indicated the presence of favorable connections for the catalysis between the Lys residue and the substrate. The recombinant chitinases produced in Pichia pastoris KM71H were purified with an apparent molecular weight of γ5 and 45 kDa, respectively, for rAoChi4κ4λ and rAoChi547β, which were identified by mass spectrometry with 41.6% and 44.β% coverage. The in vitro characterization showed that rAoChi4κ4λ shows chitinolytic activity on colloidal and insoluble chitins, as well as rAoChi547β, which proved the functionality of Lys as a catalytic amino acid and consequently the functionality of chitinases. The ideal conditions for enzymatic activity were established at pH 5 and 6 and temperature of γ0 and 40 °C for rAoChi4κ4λ and rAoChi57β, respectively. Both have stability in relation to the pH variation, being able to resume functional conformation after being subjected to extremes pH and a temperature of 60 °C. Chitinase activity is completely inhibited in the presence of Hgβ+ ions, SDS, and -mercaptoethanol and gradually in the presence of EDTA, DTT and NaCl. CD analyzes indicate a Tm of 77.γ °C for rAoChi4κ4λ and 5κ.01°C for rAoChi547β. The catalytic profile on colloidal chitin revealed the presence of GlcNAc, (GlcNAc)β, (GlcNAc)γ and (GlcNAc)4 which indicates endo and exochitinase action. The ↑max presented by rAoChi4κ4λ was 64.7 nmol.min.mg-1 and by rAoChi547β of γ.β nmol.min.mg-1, with the catalytic efficiency of rAoChi4κ4λ (4.7 nmol.mL.mg-1) 7 times greater than the efficiency catalytic analysis of rAoChi547β (0.67 nmol.mim.mg-1). Antifungal activity on phytopathogenic fungi and Candida strains was shown by the two chitinases, but none showed antibacterial activity. SEM analysis of the antifungal action of rAoChi547β on an isolate of Lasiodiplodia sp. showed the damage caused to the fungal mycelium by the protein, similar to the action of the commercial antifungal carbendazim. Regarding activity against Candida spp., analyzes should be performed to elucidate the effect of chitinase. This work highlights a new mode of action of chitinases, in which a Lys residue acts as the proton donor in catalysis. In addition, the antifungal activity shown by the chitinases of the cashew tree, represents an important information for the realization of new studies focused on the applicability of these proteins as an antifungal.